Aset Tidak Berwujud Berdasarkan PSAK 19 dan IAS 38 - Fiska Dela Mustapa; Hani Widianingrum; Nova Agnia Astika; Salma Andavira Raihana; Zahra Zelina Deaprila; Galuh Tresna Murti (CV. Ulil Albab Corp, 2022)
This article aims to find out how the rules regarding intangible assets in financial statements are based on IAS 38 and PSAK 19. Intangible assets are non-monetary assets that are identified without physical form, whereas non-monetary assets are cash held and assets to be received in cash. whose number is certain or can be determined. This article was written using the literature review method.